Candy Closure Technique for Chronic Open Infective Lateral Malleolus Bursitis. (17th March 2019) - Kim, Jin Su; Kim, Woo Jong; Young, Ki Won; Bae, Kyu Hwan; Kim, Han Hoon; Lee, Hong Seop
Abstract : The aim of this study was to report the effectiveness of the Candy closure technique as a treatment for chronic open infective lateral malleolus bursitis. From June 2014 to March 2018, we performed the Candy closure technique as a treatment for chronic open infective lateral malleolus bursitis in nine patients without secondary operation. We first performed infectious tissue debridement to control infection, and if primary closure was not possible, we performed the Candy closure technique for small wounds. The duration of the wound prior to surgery varied from 4 weeks to 2 years. Seven cases were due to infection on the bursa and two cases were ulcer-type bursitis. All the wounds were small (average, 3.80 cm 2 ; range, 2.25-4 cm 2 ) and circular. Seven wounds showed complete healing at 4 weeks after surgery, one wound showed complete healing at 8 weeks after surgery, and one wound with infected state was lost to missing follow-up. Of the seven wounds that showed complete healing, one wound recurred 6 months after surgery. The Candy closure technique is a simple method for ensuring healing and coverage of chronic open lateral malleolus bursitis, especially for small wounds with dead space.